Penggunaan Aplikasi E-Learning “HATI” dalam Pembelajaran Bahasa Arab di Perguruan Tinggi Keagamaan Islam Negeri - Hamid, M Abdul; Ifawati, Nur Ila; Charis, M Abdullah; Qomari, Nur (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
Arabic learning at the State Islamic Religious Universities has not used many applications. This is due to the unavailability of the proper application. The Arabic learning application